The Right to Health as a Claim on Dignity: Implications for State Accountability in Nigeria - Kolawole, Omowamiwa (Department of Public Law, 2022)
This thesis argues that dignity is central to the realisation of the right to health in Nigeria and shapes the relationship of the Nigerian State with its people. The thesis posits that a contextual understanding of the nature of human dignity in Nigeria is predicated on a social compact where individuals and communities accede to the preservation of the Nigerian State and its union, on the condition that it will manage the power and economic resources of the Nigerian State for the fulfilment of the welfare of every Nigerian. A contextual framing of human dignity in shaping the management of Nigeria's affairs is shown to have been jettisoned over the years. Due to the lack of political will to act for the benefit of the populace, as well as corruption and mismanagement of scarce and limited resources, the Nigerian State has been limited in its ability to fulfil its obligations to the social compact. The result has been a steady decline of the nation's health system at all levels with dire consequences for the lives and wellbeing of the Nigerian people. While important legislative intervention has been made through the National Health Act (NHA)to remedy this dire state of the Nigerian health system, it is not the panacea to the multifaceted challenges facing healthcare in Nigeria. Drawing from other jurisdictions, the thesis shows that the realisation of the NHA will be largely dependent on its social, political, and legal framing. I argue that in the face of persistent State inaction, the courts must act to provide socio-economic justice and State accountability. In providing judicial clarity and enforcement, the courts must be mindful of various pitfalls in the framing of the key legal principles of the minimum core, the test of reasonableness and requirements for the progressive realisation of the right to health. I contend that due to a flawed understanding of the nature and intent of the right to health, there is a risk of undue deference to the State's framing of its obligations and ability to meet those obligations. I propose that the right to health must instead be understood and framed as a vital claim against the State and its power, rather than as simply a social good to be provided on the whims of the ruling class and their own political priorities. I argue that to hold the State accountable to its obligations to fulfil the right to health in a manner that is people centred, the right must be framed as being nested in the maximal respect and realisation of human dignity.